Pengembangan Media Edukasi Permainan Angka Mengenai Personal Hygiene untuk Mencegah Foodborne Disease Pada Anak SD - DELA FEBIANTI; Galih Purnasari (Politeknik Negeri Jember, 2021)
Primary school children are an age group that requires nutritional needs to support their growth and development. However, poor eating habits can lead to nutritional problems. Therefore it is necessary to have nutrition intervention through nutrition education. Nutrition education becomes more effective by using attractive and easy-to-accept media. The purpose of this study was to create a Permainan Angka educational media regarding personal hygiene to prevent foodborne diseases in elementary school children. This type of research is Research and Development with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. This study uses instruments in the form of interview and observation sheets, and questionnaires. Interview and observation sheets are used to collect information and determine problems, while questionnaires are used to collect information about the needs of the Permainan Angka educational media. This research uses descriptive qualitative and quantitative techniques. Qualitative data in the form of criticism and validator suggestions are used as material for improving the product being developed. Meanwhile, the quantitative data is in the form of the assessment results from the four validators. The validation process was carried out with two material experts and two media design experts. The results of the assessment of the Permainan Angka educational media made get the final assessment very worthy of the four validators. In addition to the validation process, an acceptance test was carried out on 9 students with the results of 4 students being rated 98% (very feasible) and 5 students 100% (very feasible). The conclusion obtained is that the Permainan Angka media regarding personal hygiene to prevent foodborne diseases in elementary school children produced in this study is suitable for use as a medium for nutrition education. Keywords: Elementary School Children, Foodborne disease, Permainan Angka Educational Media, Personal hygiene.